Preliminary study of closed system transportation, rearing and observation of the eggs Oryzias javanicus (Bleeker 1854) from Tunda Island - Muh Herjayanto; Mas Bayu Syamsunarno; Nugroho Agung Prasetyo; Annisa Misykah Mauliddina; Esa Rama Widiyawan; Novita Rahmayanti; Novitasari Irianingrum; Etin Nurkhotimah; Abdul Gani; Vianka Nafisa Salsabila; Lukman Anugrah Agung (Jurnal Iktiologi Indonesia, 2020)
Wild Oryzias javanicus from Tunda Island has potential as a native Indonesian aquatic ornamental fish and a model for research in the laboratory. The preliminary stage for raising wild fish is transporting from nature to the aquacul-ture environment. Generally, to minimize fish stress during transport in a closed system, anesthetics are added to the transport media. Furthermore, good adaptation in the aquaculture environment will lead to the process of reproduction as the ultimate goal of domestication of wild fish. The research objective is to analyze the transportation of closed systems and the rearing of O. javanicus post-transportation from Tunda Island. Research observations were carried out on behavior, survival, the number of eggs, and male: female sex ratio. Transport using an additional anesthetic treatment of 0.4 mL L-1 and without anesthesia, with fish density of 16 L-1. Anesthesia used is the commercial product Ocean Free® Special Arowana Stabilizer. Transportation is carried out for 11 hours. After that, rearing post-transportation is carried out for 16 days. The results showed that the transportation of O. javanicus can use a closed system without the addition of anesthesia with a density of 16 L-1 for 11 hours. In post-transport maintenance, fish begin active swimming on day 5, swim in groups continuously on day 6, start responding to natural food on day 3 and artificial feed on day 7, and produce a final survival of 91.67%. During maintenance, O. javanicus produces 104 eggs, 0.94 ± 0.06 mm in diameter and has an attaching filaments and a non-attaching filaments in the chorion. Oryzias javanicus is an egg depositor that can spawn with a 1: 1 and 1: 2 sex ratio. Abstrak Oryzias javanicus liar asal Pulau Tunda memiliki potensi sebagai ikan hias akuaskap asli Indonesia dan model untuk penelitian di laboratorium. Tahap awal untuk memelihara ikan liar yaitu melakukan pengangkutan dari alam ke lingkungan budi daya. Umumnya, untuk meminimalkan stres ikan selama pengangkutan sistem tertutup, dilakukan penambahan anestesi ke media pengangkutan. Selanjutnya, adaptasi yang baik dalam lingkungan budidaya, akan menyebabkan terjadinya proses reproduksi sebagai tujuan akhir domestikasi ikan liar. Tujuan penelitian yaitu meng-kaji pengangkutan sistem tertutup dan pemeliharaan pascapengangkutan O. javanicus asal Pulau Tunda. Pengamatan penelitian meliputi tingkah laku, sintasan, jumlah telur dan nisbah kelamin jantan : betina. Pengangkutan mengguna-kan perlakuan penambahan anestesi 0,4 mL L-1 dan tanpa anestesi dengan kepadatan 16 ekor L-1. Anestesi yang digunakan yaitu produk komersial Ocean Free® Special Arowana Stabilizer. Pengangkutan dilakukan selama 11 jam. Setelah itu, dilakukan pemeliharaan selama 16 hari. Hasil penelitian menunjukkan bahwa pengangkutan O. javanicus dapat menggunakan sistem tertutup tanpa penambahan anestesi dengan kepadatan 16 ekor L-1 selama 11 jam. Pada pemeliharaan pascapengangkutan, ikan mulai aktif berenang pada hari ke 5, berenang berkelompok secara kontinu pada hari ke 6, mulai merespons pakan alami pada hari ke 3 dan pakan buatan pada hari ke 7, dan menghasilkan sintasan akhir sebesar 91,67%. Selama pemeliharaan, O. javanicus menghasilkan 104 butir telur, diameter 0,94±0,06 mm dan dilengkapi filamen dan fili pada korion. Oryzias javanicus adalah egg depositor yang dapat memijah dengan nisbah kelamin 1:1 dan 1:2.